DĖMESYS IR ABSTRAKCIJA. E. HUSSERLIO ATSAKAS EMPIRISTINEI ABSTRAKCIJOS TEORIJAI LOGINIUOSE TYRINĖJIMUOSE. - Šatkauskas, Ignas (Problems / Problemos, 2018)
Husserl's refutation of the empiricist theory of abstraction in the Second of his Logical Investigations required him to develop his own account of attention, since the empiricist theory explained abstraction as an achievement of attention. Nevertheless, when Husserl poses a fundamental question “what is attention?" towards the empiricist theories, he admits that phenomenology at the early stage is also incapable of giving a plausible answer. The lack of a unified sense of attention is described as a fundamental deficiency in his theory of attention. This article is an analysis of Husserl's polemic against the empiricist theory of abstraction in the Second Investigation. Four main arguments are revealed: the confusion of empirical and theoretical interests, the mistaken emphasis on the intensity of attention, the confusion of different stages and types of thematization in perceptual and conceptual levels, and the lack of a unified sense of the concept of attention. In addition, the underlying cause of deficiency of Husserl's theory of attention in Logical Investigations is identified as the lack of a notion of the universal content of attention, which would give a unified meaning to the concept of attention itself. To explain the difference between generalizing and individualizing intentions, which is essential to a phenomenological theory of abstraction, we must already possess a notion of attention.